(3JMUjd GdGfJaGY hZGjI GdGQJaGY aj hVY GdebGjjS hhVY GdCQHGYs - (3YHO GdQMef Hf YHO GddI, GdGTcQjs
(3ChdgG (B:s
(3HYO GdOjHGLg Ef CMSf eG Cdag GdeDda ef acQJg hYLR Yfg hUa GdfGXQ s
(3BNQgG (B:s
(3bHd NGJeI GdeDda hCf jPgH YfG cd ge hZe hfbeg hCf jRjOfG ef cd aGFOg hfYeg s
(3Cdag SfI (B1034 (3g` hgh EeGe HLGeY GHf Whdhfs
(3ajgG LOGhd hCTcGQ gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B366 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B16 s
Keywords: (3Gdadcs